2010
DOI: 10.1038/nprot.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Generating heparan sulfate saccharide libraries for glycomics applications

Abstract: Natural and semi-synthetic heparan sulfate (HS) saccharide libraries are a valuable resource for investigating HS structure-function relationships, enabling high-throughput glycomics studies. Owing to the difficulty of chemical or in vitro enzymatic synthesis of HS saccharides, the structural diversity displayed in saccharides from tissue or cell sources cannot be readily accessed. In contrast, saccharide libraries can be generated by partial digestion of tissue-derived HS polysaccharide chains and chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 52 publications
0
48
0
2
Order By: Relevance
“…Ϫ1 at 232 nm was used for HS experiments (28). PAGE of HS Fragments-The HS fragments were analyzed by PAGE to determine the level of purity of each one according to a previously described method (29).…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ1 at 232 nm was used for HS experiments (28). PAGE of HS Fragments-The HS fragments were analyzed by PAGE to determine the level of purity of each one according to a previously described method (29).…”
Section: Methodsmentioning
confidence: 99%
“…1A), but in contrast CXCL8 present in CF BALF (n=13) ran as a high molecular weight smear, most likely representing a GAG complexed form of the chemokine as previously described (Reeves et al, 2011b). Alcian blue, the most widely used cationic dye for demonstration of GAGs, and Azure A for sulphated material (Powell et al, 2010), confirmed the presence of GAGs in all CF BALF samples tested (Fig. 1B).…”
Section: Pa401 Reduces Cxcl8 Levels In Cf Balfmentioning
confidence: 48%
“…Gels were run at 130 V for 1.5 h and were stained with Alcian Blue Solution (Merck Millipore) or Azure A chloride stain overnight (Powell et al, 2010) and then destained with ultra pure water.…”
Section: Native Page and Western Blot Analysesmentioning
confidence: 99%
“…Porcine mucosal heparan sulfate, hyaluronic acid (HA), and chondroitin sulfate (CS C) were from Sigma; dermatan sulfate (DS) was from Iduron (Manchester, UK). Heparin oligosaccharides of degrees of polymerization (DP) DP2, DP4, DP6, DP8, DP10, and DP12 were produced, as described previously (18). A range of systematically modified heparin derivatives with different repeating units (D1-9) were prepared as described previously (Table 1) (19).…”
Section: Methodsmentioning
confidence: 99%